INOVASI PELAYANAN PUBLIK MELALUI UNIT TERPADU PENANGGULANGAN KEMISKINAN (UPT-PK) DI KABUPATEN SRAGEN - Chamid Sutikno; Indah Ayu Permana Pribadi (Economics, Social, and Humanities Journal (Esochum), 2023)
The role and duties of the government in providing public services must be able to build patterns and principles of justice. Fair public services are one of the efforts made by the Sragen Regency government to create services that are responsive to all levels of society. Integrated services in poverty alleviation are one of the efforts so that poor people can quickly get public services from the government. The implementation of public administration from a social justice perspective is where administrators, in carrying out their duties, have standards for assessing and testing government decisions. Government policy must ensure community agreement in obtaining legal protection, health protection, education, the economy, and basic community needs that are regulated in a definite, legal manner. Public Services Through the Integrated Poverty Reduction Unit (UPT-PK) in Sragen Regency, is one of the innovations carried out to optimize pro-poor based services in various integrated services for the poor which include Saraswati Card Issuance services, Jamkesda Referral Recommendations, Sintawati Card Issuance, Providing scholarships for poor families with achievements, PPA PKH Recommendations, Recommendations for non-formal education costs, Grief Compensation, Repairing uninhabitable houses, Providing Raskin assistance, Providing assistance with wheelchairs for the disabled, Clinics, Free Ambulance. With the establishment of UPT PK in Sragen Regency, it is hoped that all poor people can be served in various basic services such as education, health, and economic services. This aligns with the public service model with a new public service approach that prioritizes social justice.